Dinamika Kinerja Karyawan CV. Dadi Djoyo Malang Ditinjau Dari Organizational Citizenship Behaviour Dan Disiplin Kerja - Amelia Setyawati; Moh. Nasikh; Soehartatiek Soehartatiek; Meiman Solala Halawa (Universitas Katolik Widya Karya Malang, 2023)
The phenomenon of changing market dynamics and increasingly complex business competition, where employee performance factors become crucial for the company's success. The novelty of this research lies in exploring the contribution of organizational citizenship behavior and work discipline to employee performance in the context of local companies. This research aims to explore and analyze the dynamics of employee performance at CV. Dadi Djoyo Malang with a focus on Organizational Citizenship Behavior (OCB) and Work Discipline. The research method used is quantitative by collecting data through surveys using questionnaires to CV employees. Dadi Djoyo Malang. Data analysis was carried out using a statistical approach to identify the relationship between OCB, work discipline and employee performance. The findings of this research indicate that OCB and work discipline have a significant positive influence on employee performance at CV. Dadi Djoyo Malang. The implications of this research point to the importance of companies paying attention to and developing organizational citizenship behavior and improving employee work discipline to achieve optimal performance. This study contributes to the context of improving employee performance in local companies as well as becoming a reference for management in adopting relevant and effective policies to increase the company's competitiveness.